The opportunity space in the Lombok’s art of Gendang Beleq and its relevance to the character education - Santriawan Azmi; Hajar Pamadhi (Journal of Social Studies (JSS), 2019)
The opportunity space in the Gendang Beleq art of Lombok provides thinking and interpretation for societies who watch the show. The value of opportunity space becomes essential because it influences the social environment and how people view the artwork. The art of Gendang Beleq contains cultural values, morals, and religious values. These three values lead to a domain of character education that sustains Lombok people's life guidelines.